Anesthesia in a child with arthrogryposis multiplex congenita – how to proceed: A case report (Indian Journal of Case Reports, 2022)
Arthrogryposis multiplex congenita (AMC) consists of a heterogenous group of disorders characterized by non-progressive congenital joint contractures. They have tense skin, minimal subcutaneous tissue, and muscle mass. The anesthetic management of these children is complicated by associated congenital abnormalities, airway anomalies, congenital heart disease, pulmonary hypoplasia, and vertebral anomalies. We managed a case of AMC with bilateral contractures of both upper and lower limb and neck who presented for correction of bilateral equino varus.